IEEE INFOCOM 2014 - IEEE Conference on Computer Communications 2014
DOI: 10.1109/infocom.2014.6848050
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Dins: Insomnia therapy for duty-cycled sensor networks

Abstract: Abstract-Duty cycling mode is widely adopted in wireless sensor networks to save energy. Existing duty-cycling protocols cannot well adapt to different data rates and dynamics, resulting in a high energy consumption in real networks. Improving those protocols may require global information or heavy computation and thus may not be practical, leading to empirical parameters in real protocols. To fill the gap between the application requirement and protocol performance, we design a light-weight adaptive duty-cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In recent years, many research works have been explored to develop power-saving methods for WSNs. 4,11,[13][14][15][16][17][18][19][20] Traditional best-path energy-efficient routing protocols 2,15,16 are proposed to find minimum energy path from source node to destination to optimize energy consumption. These protocols require additional route maintenance and topology information of whole network, which may cause excessive control message cost.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many research works have been explored to develop power-saving methods for WSNs. 4,11,[13][14][15][16][17][18][19][20] Traditional best-path energy-efficient routing protocols 2,15,16 are proposed to find minimum energy path from source node to destination to optimize energy consumption. These protocols require additional route maintenance and topology information of whole network, which may cause excessive control message cost.…”
Section: Related Workmentioning
confidence: 99%
“…Besides, energy efficiency is also considered in MAC protocols. 4,11,13,14,[18][19][20] Sensor MAC (SMAC) 11 periodically puts nodes in active and sleep periods. The duty cycle is set to a low value of all nodes, so it does not adapt to network traffic change.…”
Section: Related Workmentioning
confidence: 99%
“…In these applications, the task of each sensor is to collect the information in its surrounding environment and transmit the corresponding data to the base stations of WSNs. Over the past decades, a lot of related researches have studied data gathering and transmission problems [1]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [104] proposed an off-line data-driven MAC protocol which is initialized by fixed duty-cycle duration for different packet rates as required by specific scenarios. For every packet arrival rate, it sets a specific duty-cycle duration and transmission power level.…”
Section: Chapter 3 Review Of Existing Multi-hop and Opportunistic Nementioning
confidence: 99%
“…These information is stored locally in a table, based on which every sensor node autonomously selects its duty-cycle at run-time. This procedure is not suitable for a network which experiences high trend of topology dynamics [104]. Likewise, Ayele et al [101] suggested a theoretic control model to determine the optimal duty-cycle in a wireless sensor network.…”
Section: Chapter 3 Review Of Existing Multi-hop and Opportunistic Nementioning
confidence: 99%